Current views on pathogenesis of rosacea - Barczak, Iga; Bondos, Borys; Kochan, Robert; Barczuk, Patryk; Bara, Sebastian; Dzięgielewski, Jędrzej; Bączek, Kacper; Barć, Jan; Gałajda, Elżbieta; Antonik, Jacek (Journal of Education, Health and Sport, 2023)
Rosacea is a chronic inflammatory disease that usually affects the central part of the face. The primary symptoms include facial flushing, persistent erythema, telangiectasia, inflammatory pustules and papules. Based on groups of these symptoms, four basic rosacea subtypes have been defined: erythematotelangiectatic, papulopustular, ocular, phymatous; and one variant, granulomatous rosacea. Although the pathophysiology of this disorder is not fully known, many components such as immune and neurovascular dysregulation, oxidative stress, genetic background, gut microbiome, skin microbiome as well as external aspects are thought to play a role. In this article, we present the main factors that are speculated to be involved in the pathogenesis of rosacea. Methods and materials: We reviewed the literature available on PubMed and Google Scholar using the words "rosacea”, „rosacea pathogenesis”, „demodex”, „reactive oxygen species”, „rosacea microbiome”. Summary Rosacea is a chronic dermatosis whose etiology, despite many studies, is not fully understood. Currently, an abnormal inflammatory reaction caused by excessive stimulation of TLR-2 receptors is suspected as the main factor in the pathomechanism of the disease. Vascular disorders, transmission disorders, genetic factors, skin and intestinal dysbiosis also participate in the pathogenesis of rosacea. It is assumed that exogenous factors such as diet and exposure to UV radiation also play a role in the development of the disease.